2015
DOI: 10.1007/s10456-015-9491-4
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of fatty acid-binding protein 5 on endothelial cell fate: a potential link between lipid metabolism and angiogenic responses

Abstract: Fatty acid-binding proteins (FABP) are small molecular mass intracellular lipid chaperones that are expressed in a tissue-specific manner with some overlaps. FABP4 and FABP5 share ~55 % amino acid sequence homology and demonstrate synergistic effects in regulation of metabolic and inflammatory responses in adipocytes and macrophages. Recent studies have shown that FABP4 and FABP5 are also co-expressed in a subset of endothelial cells (EC). FABP4, which has a primarily microvascular distribution, enhances angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 41 publications
0
47
1
1
Order By: Relevance
“…Interestingly, patients with lymph node metastasis had higher levels of serum FABP5, as measured by ELISA 30 . FABP5 promotes the proliferation of endothelial cells 31 . The present study showed the high expression of FABP5 in EVs from patients with high GS prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with lymph node metastasis had higher levels of serum FABP5, as measured by ELISA 30 . FABP5 promotes the proliferation of endothelial cells 31 . The present study showed the high expression of FABP5 in EVs from patients with high GS prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FABP5 is a small (15 kDa) member of the cytoplasmic FABP family and exhibits high affinity binding of long-chain FAs. There is now convincing evidence that FABP5 plays a crucial role in cancer progression, invasion and metastasis through the induction of EMT and the regulation of angiogenic responses [12,13]. However, it remains largely unknown how cervical cancer cells cope with the reprogramming of FA metabolism, thus resulting in LN metastasis.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Immunohistochemistry and immunofluorescence were performed on formalin-fixed, paraffin-embedded teratoma sections and differentiated stem cells as previously described. 27 Briefly, all primary antibody incubations were performed overnight at 4 °C. The primary antibodies were used at the following concentrations: mouse monoclonal anti-CD24 (Thermo), 1:10; mouse monoclonal anti-GATA3 (Thermo), 1:50; goat monoclonal anti-SOX17 (R&D System), 1:10; goat monoclonal anti-brachury (R&D System, Minneapolis, MN, USA), 1:10; rabbit monoclonal anti-beta III tubulin (ab18207, Abcam), 1:500.…”
Section: Methodsmentioning
confidence: 99%